Comment vivre ensemble Inside a Prison Ridden with Irreconcilable Contradictions - Silvestri , Filippo (E|C, 2024)
Prison is not a happy Babel because the many languages spoken within its walls do not blend and translate into a shared dimension of common life. Each individual confined in prison lives their own life, coming from a unique history that is different from that of their fellow inmates. There is no utopian project that can restore a carceral space to a possible redemption or conversion. Prison is the realm of the submerged and of the few ones who may one day save themselves. This essay’s analysis of the prison institution combines architectural and semiotic perspectives to demonstrate that within prison, there is no possible idiorrhythmia for those compelled to inhabit cells not meant for monks, although these cells, in certain respects, resemble those of a convent. The carceral space molds the lives of its inhabitants through paths, corridors, room, cells that operate like a mechanism that does not turn, but rather rotates around a central Panopticon axis, which is like a beacon illuminating all, yet shedding light on none.